The Influence of Communication and Organizational Commitment on The Work Achievement of Employees in Kantor Camat Beringin - Audilla Fahira (Journal of Economics and Business (JECOMBI), 2022)
Giving motivation is one of the methods used to increase the work productivity of the employees of the Beringin District Office. Failure to motivate them will result in not being able to carry out the work as desired by the employees of the Beringin Sub-district Office, this is due to their dissatisfaction at work. In carrying out motivation, it is important to pay attention to the circumstances and demands of the employees of the Beringin Head Office so that a motivation system can be established that can encourage work enthusiasm and sincerity of the workforce. Good working spirit will facilitate the achievement of company goals. Based on the description above, I am interested in compiling this research with the title "The Influence of Communication and Organizational Commitment on Work Achievement of the Office of the Banyan Head Office". After doing research, I tried to formulate the problem at the Beringin District Head Office as follows: Does motivation play a role in increasing labor productivity. Based on the problems faced by the company, the hypothesis is as follows: Communication and commitment play a role in increasing the productivity of the workforce of the Beringin District Office. The conclusion of this study is that good communication and organizational commitment have an effect on the work performance of the employees of the Beringin Head Office.